The Pyrolysis Reactor Design and The Effect of Liquid Smoke from Coconut Shell on Microbial Contamination of Tofu - Permanasari, Ayu Ratna (Bandung State Polytechnic (Politeknik Negeri Bandung), 2020)
Liquid smoke is a natural food preservative which can be made of coconut shells through the pyrolysis process. This study aimed to design a pyrolysis reactor and utilize the coconut shell waste to produce liquid smoke as a natural preservative of tofu. 1.5 kg of chopped coconut shell was pyrolyzed at 400C for 5 hours and produced 488 mL of grade 3 liquid smoke with a yield of 34.23%. The liquid smoke was then purified by extraction using ethyl acetate (1: 1 ratio) solvent and 70C temperature for 2 hours. The extract was then distilled at 80C and produced grade 1 liquid smoke. This liquid smoke had an acid content of 12.26% and a phenol content of 0.73%. This liquid smoke was then applied to tofu for 3 days and analyzed the microbial contamination. The smallest amount of microbial contamination was found in the samples of yellow tofu and white tofu coated with liquid smoke and stored in the refrigerator for 1.4 × 105 CFU / mL and 8 × 103 CFU/ml.